The Economic Performance of African-American-Owned Banks: The Role of Loan Loss Provisions - Henderson, Christopher C (American Economic Review, 1999)
The Economic Performance of African-American-Owned Banks: The Role of Loan Loss Provisions by Christopher C. Henderson. Published in volume 89, issue 2, pages 372-376 of American Economic Review, May 1999